Buprenorphine and pain treatment in pediatric patients: an update - Vicencio-Rosas E; Pérez-Guillé MG; Flores-Pérez C; Flores-Pérez J; Trujillo-Jiménez F; Chávez-Pacheco JL (Journal of Pain Research, 2018)
Erendira Vicencio-Rosas,1 María Gabriela Pérez-Guillé,2 Carmen Flores-Pérez,2 Janett Flores-Pérez,2 Francisca Trujillo-Jiménez,2 Juan Luis Chávez-Pacheco2 1Anesthesiology Department, Hospital Regional de Alta Especialidad “Bicentenario de la Independencia”, ISSSTE, Tultitlán de Mariano Escobedo, México; 2Pharmacology Laboratory, Instituto Nacional de Pediatría, Ciudad de México, México Introduction: The usual management of moderate to severe pain is based on the use of opioids. Buprenorphine (BPN) is an opioid with an analgesic potency 50 times greater than that of morphine. It is widely used in various pain models and has demonstrated efficacy and safety in adult patients; however, there are insufficient clinical trials in pediatric populations. Purpose: The aim of this study was to perform an updated meta-analysis on the implementation of BPN in the treatment of pain in the pediatric population. Methods: A bibliographic search was carried out in different biomedical databases to identify scientific papers and clinical trials with evidence of BPN use in children and adolescents. Results: A total of 89 articles were found, of which 66 were selected. Analysis of these items revealed additional sources, and the final review included a total of 112 publications. Conclusion: Few studies were found regarding the efficacy and safety of BPN use in children. In recent years, the use of this drug in the pediatric population has become widespread, so it is imperative to perform clinical trials and pharmacological and pharmacovigilance studies, which will allow researchers to develop dosage schemes based on the evidence and minimize the risk of adverse effects. Keywords: buprenorphine, opioid, analgesia, child, adverse effects, pharmacokinetics